Zaufanie interpersonalne w środowisku pracy. Analiza teoretyczna - Piorunek, Magdalena (Rocznik Pedagogiczny, 2019)
The paper Interpersonal Trust in the Working Environment. A Theoretical Analysis describes the phenomenon of trust in social relations, provides definitions and types of trust, explains the con- ditions necessary for the development of trust, and discusses the relational and personality-related aspects of trust. It also reviews the interdisciplinary literature on the subject of trust, providing a multidimensional description of trust in the workplace, in organizations. Vertical and horizontal trust in organizations is described. Presenting some trust-building models in businesses, the paper selectively describes the consequences resulting from trust vs a lack of trust in the working envi- ronment. It identifies the culture of trust and employee empowerment as desired models promoting the development of workplace relations and addresses some controversies that disrupt the functional adaptation of employees to the reality of knowledge-based organizations in the post-modern social reality.